2017
DOI: 10.1080/09687637.2017.1296933
|View full text |Cite
|
Sign up to set email alerts
|

Vapers and vaping: E-cigarettes users views of vaping and smoking

Abstract: The use of electronic cigarettes has increased markedly in recent years, however, as the popularity of e-cigarettes has increased, so has the controversy associated with their use. In this paper we report the views of a small sample of e-cigarette users focussing on the circumstances in which individuals began vaping, their reasons for continuing vaping, their perceptions of the relative harm of vaping compared to smoking, and their views as to whether their use of ecigarettes had increased their likelihood of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 21 publications
2
39
0
1
Order By: Relevance
“…Overall, there was general awareness of e-cigarettes which is not surprising, given the increasing popularity of e-cigarettes, and the high levels of awareness amongst adolescents demonstrated in previous studies(2,45). Consistent with research on older populations(46), most children could differentiate between electronic and tobacco cigarettes. Viewing smoking and vaping as distinctly different is important as it may mitigate against the re-normalisation of smoking behaviour(33,47,48).…”
supporting
confidence: 77%
“…Overall, there was general awareness of e-cigarettes which is not surprising, given the increasing popularity of e-cigarettes, and the high levels of awareness amongst adolescents demonstrated in previous studies(2,45). Consistent with research on older populations(46), most children could differentiate between electronic and tobacco cigarettes. Viewing smoking and vaping as distinctly different is important as it may mitigate against the re-normalisation of smoking behaviour(33,47,48).…”
supporting
confidence: 77%
“…Again, the results obtained in surveys with a less well-defined target population resulted in similar reported motivations for using e-cigs [ 1 , 2 , 3 , 4 ]. In addition to these (online) questionnaire studies, similar reasons for use were also reported by vapers who participated in qualitative focus group studies (e.g., [ 17 ]).…”
Section: Discussionmentioning
confidence: 78%
“…The eight young people who we focus upon in this paper were interviewed as part of a larger study in which we focussed on the perception and engagement with e-cigarettes amongst 100 non smoking vapers aged between 16 to 30 and 50 vapers [ 16 , 17 ]. The aim of this wider study was to explore attitudes towards vaping and smoking and to consider whether the availability and public visibility of e-cigarettes had resulted in smoking becoming more socially acceptable within Scotland.…”
Section: Methodsmentioning
confidence: 99%